A History of Eastern Europe 1918 to the Present : Modernisation, Ideology and Nationality - Armour, Ian D. (London, England : Zed Books, 2021)
"Why is Eastern Europe still different from Western Europe, more than a quarter-century after the collapse of Communism? A History of Eastern Europe 1918 to the Present shows how the roots of this difference are based in Eastern Europe's tortured 20th century. Eastern Europe emerged in 1918 as the 'lands between', new states whose weakness vis-à-vis Germany and Soviet Russia soon became obvious. The region was the main killing-field of the Second World War, which visited unimaginable horrors on its inhabitants before their 'liberation' by the Soviets in 1945. The imposition of Communist dictatorships on the region, ironically, only deepened Eastern Europe's backwardness. Even in the post-Communist period, its problems continue to make it a fertile breeding-ground for nationalism and political extremism. A History of Eastern Europe 1918 to the Present explores the comparative backwardness of Eastern Europe and how this has driven strategies of modernisation; it looks at the ways in which the region has served as a giant test-tube for political experimentation and, in particular, at the enduring strength of nationalism, which since 1989 has re-emerged more virulent than ever. Complete with a useful chronology, maps and a helpful glossary, this book in the essential textbook for any student of 20th-century Eastern Europe"--
The Making of "Eastern Europe" -- Melting-Pot: Eastern Europe in the First World War -- A New Europe? The Peace Settlement 1918-23 -- Problems of the Interwar Period -- Test-Tube of Ideologies: Communism -- Test-Tube of Ideologies: Conservative Authoritarianism -- Test-Tube of Ideologies: Fascism -- The East European Origins of the Second World War -- Hell's Kitchen: Eastern Europe in the Second World War -- War as Revolution: Political Consequences of the Second World War -- Great Leap Backwards: The Imposition of Communism 1944-48 -- National Communism vs. Stalinism -- The Perils of De-Stalinisation: Poland and Hungary in 1956 -- Last-Chance Saloon? The Prague Spring of -- Absurdistan, or 'Real Existing Socialism' 1968-1980s -- The Solidarity Phenomenon in Poland 1980-89 -- The Bear Vanishes: Gorbachev and the Roots of Revolution 1985-89 -- The Power of the Powerless: The Velvet Revolutions of 1989 -- The Wages of Nationalism: Soviet, Yugoslav and Czech-Slovak Break-Up -- Eastern Europe in the 21st Century: Post-Communist Modernisation -- Eastern Europe in the 21st Century: Nationalism and Geopolitics -- Conclusion: Retirement of a Concept?
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: European history; Europe, Eastern -- History -- 1918-1945 -- Textbooks; Europe, Eastern -- History -- 1945- -- Textbooks; Electronic books